The Influence of Organizational Culture and Job Satisfaction on STT Employee Performance Renatus Siantar - Akdel Parhusip; Saut Purba (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The Influence of Organizational Culture, Job Satisfaction on Employee Performance at STT Renatus Siantar. This study aims to identify and examine the influence of (1) organizational culture on the performance of STT Renatus Siantar employees; (2) the effect of job satisfaction on the performance of STT Renatus Siantar employees; (3) the influence of organizational culture and job satisfaction together on the performance of STT Renatus Siantar. The research method uses expos facto type. The research subjects consisted of 30 employees (employees) at STT Renatus Siantar, the data collection instrument consisted of a questionnaire with a Likert scale. The test results show: (1) the employee performance questionnaire contains 27 valid items with a reliability of 0.900, (2) an organizational culture questionnaire contains 26 valid items with a reliability of 0.929; (3) the job satisfaction questionnaire contains 25 valid items with a reliability of 0.928. Based on the results of testing the hypothesis, it was found that there was a positive and significant influence of organizational culture on employee performance (0.233 with thit. 8.379.) There was a significant positive effect of job satisfaction on employee performance 0.264 thit. 9.160, the results of the study also found, the tendency of organizational culture, job satisfaction is quite good. This study also found the influence of organizational culture and job satisfaction together on employee performance at FHit = 105.085 with the equation Y = 0.429 X1 + 0.396 X2 + 6.292. Based on the findings of this study, it is recommended to improve employee performance in order to consider organizational culture and employee job satisfaction